PINK1 phosphorylates Drp1S616 to regulate mitophagy‐independent mitochondrial dynamics. (2nd June 2020) - Han, Hailong; Tan, Jieqiong; Wang, Ruoxi; Wan, Huida; He, Yaohui; Yan, Xinxiang; Guo, Jifeng; Gao, Qingtao; Li, Jie; Shang, Shuai; Chen, Fang; Tian, Runyi; et al.
Abstract: Impairment of PINK1/parkin‐mediated mitophagy is currently proposed to be the molecular basis of mitochondrial abnormality in Parkinson's disease (PD). We here demonstrate that PINK1 directly phosphorylates Drp1 on S616. Drp1 S616 phosphorylation is significantly reduced in cells and mouse tissues deficient for PINK1, but unaffected by parkin inactivation. PINK1‐mediated mitochondrial fission is Drp1 S616 phosphorylation dependent. Overexpression of either wild‐type Drp1 or of the phosphomimetic mutant Drp1 S616D, but not a dephosphorylation‐mimic mutant Drp1 S616A, rescues PINK1 deficiency‐associated phenotypes in Drosophila . Moreover, Drp1 restores PINK1‐dependent mitochondrial fission in ATG5‐null cells and ATG7‐null Drosophila . Reduced Drp1 S616 phosphorylation is detected in fibroblasts derived from 4 PD patients harboring PINK1 mutations and in 4 out of 7 sporadic PD cases. Taken together, we have identified Drp1 as a substrate of PINK1 and a novel mechanism how PINK1 regulates mitochondrial fission independent of parkin and autophagy. Our results further link impaired PINK1‐mediated Drp1 S616 phosphorylation with the pathogenesis of both familial and sporadic PD. Synopsis: PINK1 regulates mitochondrial dynamics by directly phosphorylating Drp1 S616 . PINK1 phosphorylates Drp1 S616 to regulate mitochondrial fission. PINK1 regulates mitochondrial dynamics independent of both parkin and mitophagy. Reduced levels of Drp1 S616 phosphorylation are observed in fibroblasts obtained from both familial and sporadic Parkinson's disease patients. Abstract : PINK1 regulates mitochondrial dynamics by directly phosphorylating Drp1 S616 .